Influence of heat input on weld bead geometry using duplex stainless steel wire electrode on low alloy steel specimens. Issue 1 (31st December 2016) - Mondal, Ajit; Kumar Saha, Manas; Hazra, Ritesh; Das, Santanu
Abstract: Gas metal arc welding cladding becomes a popular surfacing technique in many modern industries as it enhances effectively corrosion resistance property and wear resistance property of structural members. Quality of weld cladding may be enhanced by controlling process parameters. If bead formation is found acceptable, cladding is also expected to be good. Weld bead characteristics are often assessed by bead geometry, and it is mainly influenced by heat input. In this paper, duplex stainless steel E2209 T01 is deposited on E250 low alloy steel specimens with 100% CO2 gas as shielding medium with different heats. Weld bead width, height of reinforcement and depth of penetration are measured. Regression analysis is done on the basis of experimental data. Results reveal that within the range of bead-on-plate welding experiments done, parameters of welding geometry are on the whole linearly related with heat input. A condition corresponding to 0.744 kJ/mm heat input is recommended to be used for weld cladding in practice.